Synthetic 2024 report on codesign of innovation for Senegal - Piraux, Marc; Mbaye, Banna; Belmin, Raphaël; N'Dienor, Moussa; Kouakou, Patrice Koffi; Ba, Marieme; Berre, David; Delay, Etienne; Muller, Jean Pierre; Cesaro, Jean-Daniel (2024)
This report highlights the co-design efforts undertaken within this Agroecology Living Landscape (ALL) since 2023. The objective is to foster agroecological transitions and sustainable agricultural practices. But some activities are part of the FAIR Sahel project developed in the same region since 2020, of which an agronomic assessment and farm-level modelling have been carried out as part of the project IAE.